Pengaruh Self Awareness dan Regulasi Emosi Terhadap Kesehatan Mental Remaja di Kecamatan Pondok Kelapa, Bengkulu Tengah - Aisyah Mustika; Ici Apriani; Ainun Jaria; Lailatul Badriyah (DAWUH : Islamic Communication Journal, 2024)
This study aims to look at the influence of selfawareness and emotion regulation on the mental health of adolescents in the pondok kelapa sub-district of Central Bengkulu Regency. Self awarness and emotion regulation are behaviors that are aware of the weaknesses and strengths that exist in a person and how to control emotions in a person so that it has an impact on mental health. This research uses quantitative methods, and data collection techniques by distributing a questionnaire of 30 items. The sample studied was adolescents in the pondok kelapa sub-district of Central Bengkulu Regency. This data collection amounted to 100 respondents. This research was analyzed quantitatively using spss 26 by testing correlation regression, normality test, reality test and R Square. Based on the results of this study, it shows that the effect of selfawareness and emotion regulation on the mental health of adolescents in the pondok kelapa sub-district of Central Bengkulu Regency is in the weak category, namely 35%.